Secondary analyses to assess the profound effects of empagliflozin on endothelial function in patients with type 2 diabetes and established cardiovascular diseases: The placebo‐controlled double‐blind randomized effect of empagliflozin on endothelial function in cardiovascular high risk diabetes mellitus: Multi‐center placebo‐controlled double‐blind randomized trial - Tanaka, Atsushi (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: Recent clinical trials on sodium–glucose cotransporter 2 inhibitors showed improved outcomes in patients with type 2 diabetes at a high risk of cardiovascular events. However, the underlying effects on endothelial function remain unclear. MATERIALS AND METHODS: The effect of empagliflozin on endothelial function in cardiovascular high risk diabetes mellitus: Multi‐center placebo‐controlled double‐blind randomized (EMBLEM) trial in patients with type 2 diabetes and cardiovascular disease showed empagliflozin treatment for 24 weeks had no effect on peripheral endothelial function measured by reactive hyperemia peripheral arterial tonometry. This post‐hoc analysis of the EMBLEM trial included a detailed evaluation of the effects of empagliflozin on peripheral endothelial function in order to elucidate the clinical characteristics of responders or non‐responders to treatment. RESULTS: Of the 47 patients randomized into the empagliflozin group, 21 (44.7%) showed an increase in the reactive hyperemia index (RHI) after 24 weeks of intervention, with no apparent difference in the clinical characteristics between patients whose RHI either increased (at least >0) or did not increase. There was also no obvious difference between the treatment groups in the proportion of patients who had a clinically meaningful change (≥15%) in log‐transformed RHI. No correlation was found between changes in RHI and clinical variables, such as vital signs and laboratory parameters. CONCLUSIONS: Treatment with empagliflozin for 24 weeks in patients with type 2 diabetes and cardiovascular disease did not affect peripheral endothelial function, and was not related to changes in clinical variables, including glycemic parameters. These findings suggest that the actions of sodium–glucose cotransporter 2 inhibitors other than direct improvement in peripheral endothelial function were responsible, at least in the early phase, for the clinical benefits found in recent cardiovascular outcome trials.